Non-pharmacological treatment in difficult-to-treat rheumatoid arthritis - Majnik, Judit; Császár-Nagy, Noémi; Böcskei, Georgina; Bender, Tamás; Nagy, György (Frontiers in Medicine, 2022)
Although the management of rheumatoid arthritis (RA) has improved remarkably with new pharmacological therapies, there is still a significant part of patients not reaching treatment goals. Difficult-to-treat RA (D2TRA) is a complex entity involving several factors apart from persistent inflammation, thereafter requiring a holistic management approach. As pharmacological treatment options are often limited in D2TRA, the need for non-pharmacological treatments (NPT) is even more pronounced. The mechanism of action of non-pharmacological treatments is not well investigated, NPTs seem to have a complex, holistic effect including the immune, neural and endocrine system, which can have a significant additive benefit together with targeted pharmacotherapies in the treatment of D2TRA. In this review we summarize the current knowledge on different NPT in rheumatoid arthritis, and we propose a NPT plan to follow when managing D2TRA patients.